2013
DOI: 10.1016/j.neuron.2012.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Functional Microcircuit Recruited during Retrieval of Object Association Memory in Monkey Perirhinal Cortex

Abstract: The primate temporal cortex implements neural mechanisms for memory retrieval from visual long-term storage, and memory neurons have been identified at the single-neuron level whose activities following cue presentation encode the presented object ("cue-holding" neurons) or to-be-recalled target ("pair-recall" neurons). Although these two types of neurons can potentially interact during the target recall, little is known about information flow among these neurons. We conducted simultaneous recordings of multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 73 publications
4
73
0
Order By: Relevance
“…Second, the noise contained in the data can bias the GC estimation. Previous work has shown that GC estimation of continuous time series can be strongly affected by noise, whereas spike trains are less affected (32,34). In addition, our simulations (Figs.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Second, the noise contained in the data can bias the GC estimation. Previous work has shown that GC estimation of continuous time series can be strongly affected by noise, whereas spike trains are less affected (32,34). In addition, our simulations (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…Fourth, the directional influence revealed by GC analysis is statistical in nature; thus, the observation of a Granger causal influence in the cortex does not necessarily imply the existence of direct anatomical connections between the corresponding neurons. Although GC analysis has proven informative in dissecting neuronal interactions (26,27,32,33), we note that it is difficult to exclude possible influences from hidden variables or unrecorded neurons. Although this problem has motivated several modeling studies (e.g., ref.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Learned visual associations in monkeys are reflected by association-selective representations in higher visual areas of the temporal cortex (21,22), with top-down activation by the PFC contributing to prospective representations of the choice picture to be recalled (19). Changes to stimulus-selective representations in higher sensory areas have also been reported in anesthetized starlings trained on auditory discriminations (23)(24)(25).…”
Section: Discussionmentioning
confidence: 95%